ISLAM AND SCIENCE: ITS CONCEPTION AND INSTITUTIONAL MOVEMENT IN INDONESIA - Sri Guno Najib Chaqoqo (LP3M Universitas Sains Al Qur'an, 2020)
Islam interacts and intersects with its culture either from Arab or outside of Arab. Islam revealed in Arab, in Shahrur view, as a liberation religion which is Arab didn’t introduced as a part of any dominant imperial. It is considered as the strategic role which Islam didn’t abounded which any imperial rule. Islam as a norm and values function considered to be able to interact with any culture and civilization around Arab, even in the world. Most Muslim beliefs that they able to alive in anyways they stay with difference culture. It can be seen in spread up of Muslim outside Arab moreover when they intersect with Persian and Byzantine which both of them more civilized in all of aspects. Islam as a religious value, then, intersect with science in the new culture. Thus how Islam interact with science? This paper tries to elaborate about early intersection of Islam and Hellenism till nowadays era.